2002
DOI: 10.1007/s11661-002-0173-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic description of the Cu-Al-Sn system in the copper-rich corner

Abstract: Thermodynamic optimization of the Cu-Al-Sn system is made using classical thermodynamic models for describing the properties of the individual phases of the system. The optimization is limited to the copper-rich corner of the system, the gamma phase of the Cu-Al and Cu-Sn systems being the remotest phase included in the analysis. The data of the pure components and the binary systems are taken from the previously assessed Scientific Group Thermodata Europe (SGTE)-compatible descriptions, although a slight reop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 21 publications
3
38
1
Order By: Relevance
“…(6a) are also zero. In contrast, the binary L (2) CuSn data, obtained by Witusiewicz et al [10], Miettinen [12], and in this work using a multiple regression on Hultgren' s original data [11], are not zero (see Table 2). Therefore, an equation assuming a non-zero L (3) data must be derived.…”
Section: Determination Of Thermodynamic Quantities Of Mixing By Convementioning
confidence: 55%
See 3 more Smart Citations
“…(6a) are also zero. In contrast, the binary L (2) CuSn data, obtained by Witusiewicz et al [10], Miettinen [12], and in this work using a multiple regression on Hultgren' s original data [11], are not zero (see Table 2). Therefore, an equation assuming a non-zero L (3) data must be derived.…”
Section: Determination Of Thermodynamic Quantities Of Mixing By Convementioning
confidence: 55%
“…[8][9][10][11][12]. Table 2 gives a comparison of the binary L-data taken from all of these sources while Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6, the Gibbs excess free energies of various binary alloys are given. [56][57][58][59][60][61][62] It is found that liquid Sn-Ag and Sn-Cu have negative values.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%